Bioenergy—The slope of enlightenment. Issue 7 (16th July 2020) - Long, Stephen P.
Abstract : With this month's issue, GCB Bioenergy unveils its new journal masthead: Global Change Biology— Bioenergy Bioproducts for a Sustainable Bioeconomy.